Overcoming Rent by Using Rent: The Challenge of Development - Hartmut Elsenhans (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2004)
The article tracks the current crises of development theory in the understanding of the differences in political economy of developed capitalism (rising mass incomes) and underdeveloped economies (labor surplus and rent). The challenge of rents consists in spontaneous tendencies of its wasteful use for blocking development, which do, however, not exclude its possible use for the elimination of marginality. A convoy model of globalization with world wide full employment and an underconsumptionist model are distinguished. In the convoy model, an underdeveloped economy reaches full employment on the basis of devaluation. In the underconsumptionist model, devaluation-driven export-oriented industrialization does because of its too small impact not lead to the scarcity of average skilled labor. Leading industrialized countries react to the new competitiveness of catching-up economies through the implementation of wage restraint and industrial policies. Rent bounces back. Establishing a convoy model requires development policies characterized by an intelligent mix of rising mass incomes, reduced rents and devaluation-driven industrialization together with state support for investment.
Keywords: 330